Membrane lipid environment: Potential modulation of chemokine receptor function. (September 2018) - Thelen, Marcus; Legler, Daniel F.
Highlights: Membrane lipid composition influences chemokine receptor activity. Cholesterol is critical for chemokine binding, receptor stability & oligomerization. Tuning chemokine receptor signaling by lipids. Abstract: Migration of leukocytes is typically mediated by G protein-coupled receptors (GPCRs) upon activation by specific ligands that range from small peptides, chemokines to a variety of lipidic molecules. The heptahelical receptors are highly dynamic structures and the signaling efficiency largely depends on the discrete contact with the ligand. In addition, several allosteric modulators of receptor activity have been reported, which do not induce migration by themselves. Another important mechanism modulating the activity of GPCRs is their local environment. Not only the membrane lipid composition influences the activity, but also direct binding of lipids, in particular cholesterol, was shown to alter receptor signaling properties. Recent findings indicate that also chemokine receptor activity is modulated by membrane lipids. In this short review we discuss this new paradigm and potential consequences for chemokine-induced migration.